Immunogenicity of intramuscular MF59-adjuvanted and intradermal administered influenza enhanced vaccines in subjects aged over 60: A literature review - Camilloni, Barbara; Basileo, Michela; Valente, Stefano; Nunzi, Emilia; Iorio, Anna Maria (Human vaccines & immunotherapeutics, 2015)
Because of the age-related immune system decline, 2 potentiated influenza vaccines were specifically licensed for the elderly: Fluad®, an MF59-adjuvanted vaccine administered intramuscularly (IM-MF59), and Intanza 15mcg®, a non adjuvanted vaccine administered intradermally (ID). The objective of this paper was to conduct a systematic review of studies that evaluated antibody responses in the elderly following immunization with IM-MF59 or ID vaccines. The two potentiated vaccines induced immune responses satisfying, in most instances, the European Medicine Agency immunogenicity criteria, both against vaccine antigens and heterovariant drifted strains. Considering pooled data reported in the articles analyzed and papers directly comparing the 2 vaccines, the antibody responses elicited by IM-MF59 and ID were found to be generally comparable. The use of IM-MF59 and ID vaccines can be proposed as an appropriate strategy for elderly seasonal influenza vaccination although further studies are required for a more complete characterization of the 2 vaccines.